Evaluation of Holistic Childbirth Education Program to Reduce Complications and Improve Quality of Life for Couples in Urban Purwakarta - Karmilah, Karmilah; Lailia Syhabudin, Sifa (Green Publisher Indonesia, 2025)
The holistic childbirth education program aims to prepare couples physically, psychologically, and emotionally for the childbirth process, thereby reducing the risk of complications and improving quality of life. This study evaluated the effectiveness of the program in urban Purwakarta. The research design used a quasi-experimental approach with a pretest-posttest design involving 80 couples who participated in the holistic childbirth education program at three maternity clinics. Data were collected through childbirth knowledge and anxiety questionnaires, medical records, and interviews. The results showed a 25% reduction in childbirth complications, a 40% increase in couples' knowledge, and a 30% decrease in anxiety levels. In conclusion, the holistic childbirth education program was proven effective in improving couples' readiness and postpartum quality of life.